The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013 Physics Education Research Conference Proceedings 2014
DOI: 10.1119/perc.2013.pr.016
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Educational Transformation: Findings from a Survey of Past Participants of the Physics and Astronomy New Faculty Workshop

Abstract: Abstract:We surveyed past participants of the Physics and Astronomy New Faculty Workshop to learn more about their experiences. Survey questions were based on areas that emerged as salient from a longitudinal three year study of 15 workshop participants. Questions included: current practice, experiences with student resistance to reform, perceptions of available curricular and support resources, perceptions of local climate, and demographics of both faculty and their students. In this paper we report on an ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…(2003 ) characterized students’ perceptions and attitudes toward student-centered learning environments and found that, while many students held positive views toward these teaching methods, ∼40% of students reported having more cynical views in a previous class (e.g., the instructor does not want to teach us and is making us do all the work). Similarly, a study of college physics instructors found that as few as 19% of instructors saw decreases in end-of-semester student evaluations—attributed to student resistance—while nearly 50% saw increases in evaluations after implementing research-driven teaching methods ( Dancy et al ., 2014 ). If it is the case that a small subset of instructors face student resistance while the majority do not, then what is different about the learning environments in these classrooms?…”
Section: Introductionmentioning
confidence: 99%
“…(2003 ) characterized students’ perceptions and attitudes toward student-centered learning environments and found that, while many students held positive views toward these teaching methods, ∼40% of students reported having more cynical views in a previous class (e.g., the instructor does not want to teach us and is making us do all the work). Similarly, a study of college physics instructors found that as few as 19% of instructors saw decreases in end-of-semester student evaluations—attributed to student resistance—while nearly 50% saw increases in evaluations after implementing research-driven teaching methods ( Dancy et al ., 2014 ). If it is the case that a small subset of instructors face student resistance while the majority do not, then what is different about the learning environments in these classrooms?…”
Section: Introductionmentioning
confidence: 99%
“…Despite this movement toward developing and supporting systemic reform in STEM undergraduate education, a majority of university STEM faculty members who teach undergraduate science and engineering classes have remained inattentive to the shifting landscape. Student-centered, evidence-based teaching practices are not yet the norm in most undergraduate STEM education courses, and the desired magnitude of change in STEM pedagogy has not materialized (Anderson et al, 2011;Dancy et al, 2013;Eiseman & Fairweather, 1996;Fairweather & Beach, 2002;Fisher, Zeligman, & Fairweather, 2005;.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this movement toward developing and supporting systemic reform in STEM undergraduate education, a majority of university STEM faculty members who teach undergraduate science and engineering classes have remained inattentive to the shifting landscape. Student-centered, evidence-based teaching practices are not yet the norm in most undergraduate STEM education courses, and the desired magnitude of change in STEM pedagogy has not materialized (Anderson et al, 2011;Dancy et al, 2013;Eiseman & Fairweather, 1996;Fairweather & Beach, 2002;Fisher, Zeligman, & Fairweather, 2005;.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a key element of our strategy was to leverage social networks in the form of faculty learning communities (FLCs) to enact cultural change. Evidence suggests such networks might be necessary for the dissemination of reformed practices and development of emergent practices (Dancy, 2013;Kezar, 2014), by providing social incentives for greater change work (Bouwma-Gearhart, 2012). In our model, all mentor-apprentice teams participate in interdepartmental FLCs (and some in intradepartmental FLCs).…”
Section: Case Studies-projects At the Institution Levelmentioning
confidence: 99%